Pengaruh Lokasi, Penggunaan Informasi Akuntansi, dan Modal Usaha terhadap Keberhasilan UMKM - Nur Ruswati, Wahyu; Hendri, Nedi; Kurniawan, Angga (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of location, use of accounting information, and business capital on the success of MSMEs. This type of research uses quantitative research with a descriptive approach. The sampling technique in this study uses a purposive sampling technique using several criteria so that 30 respondents from the Banana Chips Industry Center in Bandar Lampung are obtained. Data analysis in this study uses SPSS testing. The results of this study indicate that the influence of location has an effect on the success of MSMEs in the Chips Industry Center in Bandar Lampung, the use of accounting information has an effect on the success of MSMEs in the Banana Chips Industry Center in Bandar Lampung, and business capital has an effect on the success of MSMEs in the Banana Chips Industry Center in Bandar Lampung.